PENGARUH PEMBERIAN LEV AMISOL PRA VAKSINASI AVIAN INFLUENZA (Al) TERHADAP RESPON KEBAL AYAM PETELUR - Lili Zalizar (Faculty of Animal Science, Universitas Brawijaya, 2009)
Success of vaccination to certain diseases depends of immune response condition. One of drug that can act as immunomodulator is levamisol. The purpose of the reseach was to find out effect of levamisol pre AI vaccination to immune response of layer. The research used experimental method and was based on Randomized Completely Design. One hundred and fifty Days Old Chicks (DOC) were divided into three goups of treatments. First goup was without levamisole (control goup).The second and third goup were given levamisol at 1 mg/50 kg body weight respetively for three and six days, respectively. Lymphocyte cell was evaluated between two to five weeks after Al vaccination. Leucocyte cells like monocyte and neutrophyl (heterophyl) were examined two days after Al vaccination.Result of the research showed that levamisole treatment pre AI vaccination can highly significant increase non specific immune response with remarkable increase in monocyte cells. But its effect to total of neutrophyle cells did not significant. Levamisole treatment pre Al vaccination Al can also highly significant increase celluler specific immune response indicating by a remarkable increase in lymphocyte cells. Based of the result, it is concluded to necessarily use levamisole pre Al vaccination to increase immune response in chickens against Al natural infection (JIIPB 2009 Vol 19 No 1: 10-19)Keywords : levamisole, vaccination, immune response, layer